MAIN APPROACHES TO SHIP TRAFFIC CONTROL ON COURSE (Transport systems and technologies, 2022)
The management of the vessel's course on the course is an important maritime quality that determines the effectiveness of the vessel's management. The environmental conditions in which course management tasks need to be addressed are of a different nature - limited visibility, stormy weather, icing, shallow water, tidal phenomena, narrow conditions, the presence of other vessels, and so on. All these aspects cannot be comprehensively considered by traditional mathematical methods, ensuring the necessary adequacy of the actual process.This paper highlights the existing approaches to the management of ship traffic on the course such as course management, disturbance management, ship traffic management on the basis of long-term forecasting, proportional-integral-differential (PID) law of control (deviation control), intellectual approaches to court management, in particular, synergetic approach, use of neural networks, fuzzy logic and evolutionary (genetic) algorithms-languages.
Keywords: controllability, perturbation, deviation, PID law.